Development of Foot-and-Mouth Disease Virus-Neutralizing Monoclonal Antibodies Derived From Plasmablasts of Infected Cattle and Their Germline Gene Usage - Li, Kun; Wang, Sheng; Cao, Yimei; Bao, Huifang; Li, Pinghua; Sun, Pu; Bai, Xingwen; Fu, Yuanfang; Ma, Xueqing; Zhang, Jing; Li, Dong; Chen, Yingli; et al. (Frontiers in Immunology, 2020)
Cattle are susceptible to foot-and-mouth disease virus (FMDV), and neutralizing antibodies are critical for protection against FMDV infection in this species. However, more information is needed on the host specific antigenic structure recognized by the FMDV-specific monoclonal antibodies (mAbs) and on the functional properties of the mAb that are produced in the natural host, cattle. Herein, we characterised 55 plasmablast-derived mAbs from three FMDV-infected cattle and obtained 28 FMDV-neutralising antibodies by the single B cell antibody technique. The neutralising mAbs (27/28) mainly recognised conformational epitopes that differ from the well-characterised immunodominant antigenic site 1 of FMDV as defined by murine mAbs. Of these FMDV-neutralising mAbs, 13 mAbs showed intra-type broadly neutralising activity against the three topotypes of FMDV serotype O (ME-SA, SEA and Cathay topotypes). Moreover, all these intra-type broadly neutralizing antibodies competed with sera from FMDV infected or vaccinated cattle, which indicates their binding to native dominant epitopes, as revealed by a blocking ELISA. We further analysed the germline V(D)J gene usage of the 55 FMDV-specific mAbs and found cattle IgG antibodies containing ultralong HCDR3 were exclusively restricted to usage of the germline gene segment VH 1-7*02. In addition, the restricted germline gene segments of VH 1-7*02 and VL1-47*01 or 1-52*01 pairing were observed in all IgG antibodies with ultralong HCDR3. Furthermore, antibodies with longer HCDR3 were more inclined to display FMDV-neutralising activity. This study presents a novel method for screening FMDV-specific cattle mAbs which then provide the most useful tools for studying FMDV antigenic structure and variation.